Cannabis-derived cellulose acetate electrospun membranes for therapeutic dressings: extraction, characterization, and prototype development - Lara, Adriana; Cely, Erika; Gómez-Pachón, Edwin; Rubiano-Navarrete, Andres; López, Alex; Antosik, Adrian Krzysztof; Vendrell, Xavier; Serafin, Jarosław (Frontiers in Chemistry, 2025)
This work reports the development of electrospun cellulose acetate (CA) membranes derived from Cannabis sativa biomass for potential use in therapeutic dressings. Cellulose was extracted from cannabis stalks using alkaline pulping and bleaching, followed by homogeneous acetylation to obtain CA with controlled substitution. CA solutions (13%–25%) were electrospun under varying parameters, and the 17% formulation yielded the most homogeneous, bead-free nanofibers. The resulting membranes were characterized using FTIR, XRD, Raman spectroscopy, UV–Vis spectrophotometry, and SEM. FTIR and Raman confirmed acetylation through characteristic ester and methyl group vibrations. XRD revealed reduced crystallinity in CA compared to native cellulose. SEM analysis showed uniform fiber networks with diameters between 500 and 800 nm. A bilayer dressing prototype was fabricated by integrating the electrospun membrane with a medical-grade silicone adhesive. Adhesion performance was evaluated on synthetic skin using a FINAT-standardized 180° peel test. The membranes demonstrated adequate mechanical cohesion and conformability, supporting their application as sustainable, plant-based biomedical patches.